1983
DOI: 10.1044/jshr.2601.30
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Effects in the Measurement of Hearing-Impaired Speakers' Intelligibility

Abstract: Previous research has indicated that hearing-impaired speakers' intelligibility scores are better when sentences are used than when word lists are used as speech material in word identification tests. The speech intelligibility of 20 hearing-impaired speakers was measured with word identification tests using isolated words (W-22 monosyllables) and words in sentences context (CID sentences). Analysis of individual speaker' intelligibility data revealed that sentence intelligibility scores were higher than word … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 0 publications
2
26
0
Order By: Relevance
“…Their data suggest that when intelligibility was between 15 and 30%, there was no longer a benefit to words in sentences over words in isolation. Research on speakers with hearing impairment supports this conclusion [5] . Studies examining speakers with severe dysarthria are less clear, indicating that individual speaker characteristics may play an important role in determining the difference between sentence and word intelligibility.…”
Section: Word Vs Sentence Intelligibilitysupporting
confidence: 66%
“…Their data suggest that when intelligibility was between 15 and 30%, there was no longer a benefit to words in sentences over words in isolation. Research on speakers with hearing impairment supports this conclusion [5] . Studies examining speakers with severe dysarthria are less clear, indicating that individual speaker characteristics may play an important role in determining the difference between sentence and word intelligibility.…”
Section: Word Vs Sentence Intelligibilitysupporting
confidence: 66%
“…has an important effect on intelligibility (Miller et al 1951). This also holds for hearing-impaired and deaf speakers (Monsen 1983;Sitler et al 1983). For a group of severely or profoundly hearing-impaired adolescent speakers, for example, Monsen (1983) showed that adding linguistic complexity to the test material diminished word intelligibility, whereas adding contextual information to the material boosted intelligibility.…”
Section: Introductionmentioning
confidence: 80%
“…In rating procedures, for example, the listener's task is to rate the intelligibility of a sample of connected speech (e.g., Schiavetti et al 1981;Doyle 1987;Samar & Metz 1988;Allen et al 1998;Loundon et al 2000;Calmels et al 2004;Huttunen & Sorri 2004;Peng et al 2004;Klop et al 2007). In tests with an item identification task, on the other hand, the linguistic unit to be identified may consist of phonemes, words, or sentences, whereas the linguistic context may also vary (e.g., Monsen 1983;Sitler et al 1983;Boothroyd 1985;Metz et al 1990;Osberger et al 1993;Gould et al 2001;Chin et al 2001;Peng et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…One explanation for this finding relates to the stimulus material that children produced. Specific linguistic characteristics of speech stimuli can have a significant impact on listener performance; for example, words tend to be less intelligible than sentences (Hustad et al, 2012;Miller, Heise, & Lichten, 1951;Sitler, Schiavetti, & Metz, 1983). One reason for this phenomenon may be that listeners are able to apply their linguistic knowledge, including semantic and syntactic expectations, more readily to a sentence transcription task than to a word transcription task.…”
Section: Variability Of Intelligibility Scoresmentioning
confidence: 99%